Die Genossenschaftliche Institutssicherung – ein notwendiges Instrument zur Stärkung des Kundenvertrauens und des Risikomanagements im dezentralen Bankenverbund - Peter Gleber (IBF - Institut für Bank- und Finanzgeschichte, 2017)
Cooperative Institutional Protection – a Necessary Instrument for Strengthening Customer Trust and Risk Management in Local Banking Groups: The protection scheme of the cooperative financial network goes back to the guarantee funds of the German Volksbanken, the world's oldest privately-financed protection system for banks. The core task of institutional protection is to protect the cooperative banks and hence the protection of the member's and customers' deposits, investments and savings. The local roots of the credit cooperatives rest in the 19th century. During the so-called formative phase, protection schemes were established for the newly-created cooperative lending networks of Volksbanken and rural cooperative banks, which have been a joint cooperative financial network since 1972. Since that time, the cooperative banks' combined protection scheme has developed into a unique protection system with complex tools for risk management.
Keywords: G21; N14; N24; N34; N94; P13; 330